(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:Scholars in the past and the present have been studying the topics of the sciences of the Qur’an, and in their writings they have relied on many books of hadith and tradition from the sayings of the Companions, and they have transmitted the authentic and honorable hadiths from the narrators, and among these authors is Sheikh Muhammad al-Sabzwari, who died in the year (T: 1409 AH), where he was quoted in his book (Al-Jadid). In the interpretation of the Glorious Qur’an) information from several sources and many resources, and among these resources are the honorable hadiths from the books of hadith, and because of the importance of this book, I wanted to explain the investigations of the sciences of the Qur’an in its interpretation, including (revelation), and the research includes the research on the descent of the revelation, and it is divided into three demands, including(Revelation linguistically and idiomatically, images of revelation and its divisions, revelation in the Holy Qur’an).Keywords: Sabzwari, revelation, images of revelation, sections of revelation.The research is extracted from a master’s thesis